The role of interprofessional education (IPE) for medical students in pharmacology subject - Alfian Novanda Yosanto; Sufi Desrini; Wulandari Berliani Putri (Indonesian Journal of Pharmacology and Therapy, 2020)
Interprofessional education (IPE) is a learning method that allows the clinical clerkship to study together, exchange knowledge, and develop the skill that is needed in interprofessional collaborative work practice. This article analyzed the elements within IPE including background, operational definition, goals and benefits, implementation, as well as competency in IPE. Furthermore, the role of IPE for medical students especially in pharmacology subject was discussed. In summary, interprofessional collaboration (IPC) is needed to answer the high demand and complexity of patient problems in minimizing medication errors due to low IPC. The IPE is an early step towards realizing IPC where each profession can understand each other’s roles and responsibilities to achieve comprehensive patient health.